(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article dwells on lexical system of stylistic devices. Much attention is paid to the use of different types of metaphor, as the key point of expression of author’s intensions. As there are many theoretical and practical works on stylistics of Tajik and English languages, but still not all the occasional peculiarities of stylistic lexical means have been researched, we consider this topic to be actual for our research. Thus, we intend to reveal structural and semantic peculiarities of functioning of metaphor and simile in literary works and their common and distinctive tendencies in Tajik and English languages.